Impact of the COVID-19 pandemic on violent extremism and organized crime in the Republic of Serbia - Đorić Marija; Životić Ilija (Srpska Politička Misao)
The subject of research is the impact of the COVID-19 pandemic on violent extremism and organized crime in the Republic of Serbia. The authors used the method of document content analysis and quantitative methods (surveys) for research purposes. The time of the research included the most intense period of the pandemic, and the authors investigated the situation in the Republic of Serbia from March 2020, when the virus was first registered, to mid-2021. The initial hypothesis in the research is that violent extremism and organized crime adapt very quickly to new social changes, which makes them resilient to many social crises. Serbia has a long history of fighting etno-separatist extremism (e.g. the KLA terrorist organization), but the COVID-19 pandemic has intensified the growth of other forms of extremism, such as religious, left-wing, while special attention is focused on right-wing extremism. Namely, the authors determined that in addition to the old generators (what is the post-conflict legacy), we also have two new crucial generators of the extreme right - the COVID-19 pandemic and the migrant crisis. All the fundamental issues on which the extreme right-wingers built their ideology (such as Kosovo and Metohija, the friend-enemy dichotomy) were pushed aside during the pandemic, in order to actualize the problems concerning the "infestation of migrants", conspiracy theories, vaccinations, 5G networks and of panic fear for the survival of the nation. Organized crime also found a way to adapt to the pandemic, and some new areas appeared that criminals quickly prioritized, such as the trade-in of deficient medical equipment, falsification of PCR tests, etc. Drug trafficking was particularly intense, and the Customs Administration seized during the pandemic from 01.03.2020 to 01.08.2021 5630.53 grams of cocaine, which is 60 percent more than in 2019; 2063 grams of heroin, which is a drop to only 5 percent of the total seizure in 2019. In the same period, 1,180 tablets of ecstasy and MDMA were seized, which is five times more than in 2019, as well as 36 weapons. The conclusion is that the COVID-19 pandemic had a significant impact on the change in the functioning of violent extremism and organized crime, thus confirming the initial hypothesis of the author, that these are "tough phenomena" that adapt very quickly and easily to emerging social crises. which is down to just 5 percent of total seizures in 2019. In the same period, 1,180 tablets of ecstasy and MDMA were seized, which is five times more than in 2019, as well as 36 weapons. The conclusion is that the COVID-19 pandemic had a significant impact on the change in the functioning of violent extremism and organized crime, thus confirming the initial hypothesis of the author, that these are "tough phenomena" that adapt very quickly and easily to emerging social crises. which is down to just 5 percent of total seizures in 2019. In the same period, 1,180 tablets of ecstasy and MDMA were seized, which is five times more than in 2019, as well as 36 weapons. The conclusion is that the COVID-19 pandemic had a significant impact on the change in the functioning of violent extremism and organized crime, thus confirming the initial hypothesis of the author, that these are "tough phenomena" that adapt very quickly and easily to emerging social crises.